O efeito do pH, meio de cultura e fase de crescimento na produção de vesículas extracelulares de Escherichia coli ATCC 8739 - Lauande, Ana Cristina Leal (2025)
Bacterial extracellular vesicles are lipid bilayer nanostructures released by Gram negative and Gram-positive bacteria throughout their life cycle. These vesicles originate from the cell envelope membranes and contain a wide variety of biomolecules, reflecting the composition and metabolic state of the bacterium at the time of their formation. Due to their efficiency in transporting and internalizing molecules into specific cells and tissues—similar to the performance of synthetic liposomal systems—these structures have been explored in various biotechnological applications. In nanomedicine, extracellular vesicles from Gram-negative bacteria are frequently used as adjuvants in vaccine formulations due to their immunogenicity. However, the presence of lipopolysaccharides (LPS) in the membrane can confer high reactogenicity, which may limit their use in formulations requiring low immunogenicity. The pH of the culture medium is one of the factors influencing bacterial vesiculation, promoting membrane modifications that can impact the composition of the vesicles produced. Additionally, some bacteria can modulate LPS expression in response to variations in medium pH, which may alter the amount of this molecule in the released vesicles. This work aims to investigate the influence of pH, culture medium, and growth phase on the production of membrane vesicles in cultures of the non-pathogenic strain Escherichia coli ATCC 8739, evaluating how these variations in culture conditions affect the concentration of vesicles, size, surface charge, protein concentration, and LPS content in the produced vesicles. For this purpose, E. coli ATCC 8739 was cultured in two media—minimal and Luria Bertani—buffered at pHs 6.0, 7.0, and 8.0. Aliquots were collected during the logarithmic and stationary phases under each culture condition to compare vesiculation profiles and LPS production. Vesicle isolation was performed by differential ultracentrifugation, applied in two successive cycles at 150,000 × g for 3 hours. The vesicles were characterized for size and the presence of subpopulations by tunable resistive pulse sensing (TRPS), surface charge by zeta potential, morphology by transmission electron microscopy, total protein quantification by the bicinchoninic acid assay, and endotoxin quantification by the Limulus amebocyte lysate (LAL) assay. The results indicate that the complex medium favored vesicle production compared to the minimal medium, resulting in smaller, more homogeneous vesicles with a more electronegative surface charge, higher protein concentration, and lower LPS concentration. The pH influenced protein concentration, which was higher at alkaline pHs, and LPS concentration, which was higher at acidic pHs. The growth phase influenced vesicle heterogeneity, with a more heterogeneous profile observed during the logarithmic phase. In the stationary phase, greater stability and protein enrichment were observed, particularly in the complex medium. The results of this study highlight that the culture medium and pH are determining factors for the composition and stability of extracellular vesicles from Escherichia coli ATCC 8739, influencing protein and LPS concentrations.